BOOK REVIEW OF THE HAPPINESS PROJECT WRITTEN BY GRETCHEN RUBIN - Prasetyo, Mochammad Afrizal (LANTERN (Journal on English Language, Culture and Literature), 2016)
This book review analyzes the strengths and weaknesses of Gretchen Rubin’s The Happiness Project. The Happiness Project is a novel about how to pursuit happiness in life. The writer’s purpose of this review is to explore the strengths and weaknesses through its intrinsic elements, like theme, characters, plot, setting, and point of view so that there are beneficial aspects for readers. The writer usesCarl Gustav Jung’s theoryto examine the main character of the novel, Rubin. This novel has 12 chapters in which each chapter represents a new month.From this process, we can learn a lot about life that does not always rely on the material and money